Case report: Paraneoplastic lower motor neuronopathy associated with a malignant liver tumor - Xu, Chaowei; Wu, Hanfan; Chen, Jian (Frontiers in Neurology, 2024)
Paraneoplastic lower motor neuronopathies (LMNs) have rarely been reported with malignant liver tumors. A 71-year-old man developed chronic progressive upper limb and cranial nerve paralysis. Electromyography examination suggests chronic progressive neuronal damage involving the right C4–T1 nerve root innervated muscle and the right sternocleidomastoid muscle. Magnetic resonance imaging suggested the presence of a malignant liver tumor. His serum was positive for anti-Yo antibodies. Hepatic artery chemoembolization was performed, followed by treatment with pembrolizumab and lenvatinib. The patient’s condition improved, and paraneoplastic LMNs were diagnosed. Paraneoplastic causes should be considered in the differential diagnosis of chronic progressive LMNs. A combination of surgical treatment and immunotherapy may result in a favorable outcome.